Competition policy and MERCOSUR - Rowat, Malcolm (World Bank WashingtonUS, 1997)
Provides an assessment of the legislative/institutional and enforcement effectiveness of the competition (antitrust) framework of the four MERCOSUR countries including specific recommendations for reform, drawing analogies where appropriate, to the experience of the European Union and NAFTA.